Pengaruh Desa Wisata Terhadap Perubahan Guna Lahan, Sosial Dan Ekonomi Di Gampong Nusa, Kabupaten Aceh Besar, Aceh - Siti Salsabila Ulfah; Putra Rizkiya; Zahrul Fuady; Zainuddin Zainuddin (Jurnal RAUT, 2021)
The tourism village in Gampong Nusa, Aceh Besar Regency was initiated by women group. It started as a waste processing program in 2006. Then it became a community-based tourism village in 2015, offering beautiful view and Acehnese traditional rural life. A growing number of local and international tourists visited the village. The tourism village can cause changes in land use and social-economic aspects. This research studies the effect of tourism village in Gampong Nusa on land use, social and economic changes using quantitative and qualitative data. The analysis used is descriptive qualitative analysis. The image interpretation analysis is utilized to study the land-use change. This study found that the tourism village in Gampong Nusa caused a land-use conversion from non-built-up area to built-up area to support tourist needs such as accommodation. It also affects social changes. Attitude change is shown by the growing community support for tourism and its openness towards tourists. The behavior changes is represented by the high interactions with tourists. The changes in economic aspects are the growth of job opportunities and income. The community-based tourist village program with positive impact on the economy, social and land use show that Gampong Nusa has implemented a sustainable tourism concept.